Brainstem abscess of undetermined origin: microsurgical drainage and brief antibiotic therapy - Hamamoto Filho, Pedro Tadao; Zanini, Marco Antonio (São Paulo Medical Journal, 2014)
CONTEXT: Solitary brainstem abscesses are rare and they are usually associated with other infections. They are severe conditions with high morbidity and mortality. The surgical options are stereotactic aspiration and microsurgical drainage. Systemic antibiotic therapy is used for more than six weeks. CASE REPORT: We present the case of a young man with a solitary abscess at the pons, without other systemic infections. The patient was treated by means of microsurgical drainage and antibiotic therapy for three weeks. His postoperative recovery was good. CONCLUSIONS: A microsurgical approach may be considered to be an important option for large abscesses that are multiloculated, close to the surface or contain thick fluid. Complete emptying of the purulent accumulation may diminish the required duration of antibiotic therapy.